Pengaruh Kepemilikan Asing , Leverage, Cash Holdings Dan Debt Maturity Terhadap Kinerja Keuangan Perusahaan - Murti Sari Dewi; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the effect of foreign ownership, leverage, cash holding and debt maturity on financial performance in property and real estate companies listed on the Indonesia stock exchange (idx) in the period 2014-2018. This study is categorized as causative research. The population in this study are property and real estate companies listed on the Indonesia stock exchange (idx) in the period 2014-2018. By using purposive sampling method, there were 24 companies as the research’s sample. The type of data used is secondary data and used is panel regression analysis. The results of this study indicate that foreign ownership, cash holding and debt maturity has no significant effect on financial performance, only leverage has significant effect on financial performance